1998
DOI: 10.1063/1.368028
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of CdS and CdSe films deposited on vibrating substrates

Abstract: Polycrystalline cadmium sulphide (CdS) and cadmium selenide (CdSe) films are deposited on glass substrates kept at room temperature using the method of resistive heating. In this article, the influence of substrate vibrations at ultrasonic frequency during deposition on the electrical properties of the films is discussed. The resistivity of the films has been studied as a function of temperature, and the activation energies have been determined for the films deposited on a vibrating substrate and on a static s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…This is true both for MOCVD grown films and the films deposited by thermal evaporation (see Tables 1 and 2), and is in accordance with earlier reported data [8,20]. Although the two deposition techniques showed similar results and tendencies, for the films obtained by thermal evaporation, slightly higher TCR values and lower resistances were obtained.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This is true both for MOCVD grown films and the films deposited by thermal evaporation (see Tables 1 and 2), and is in accordance with earlier reported data [8,20]. Although the two deposition techniques showed similar results and tendencies, for the films obtained by thermal evaporation, slightly higher TCR values and lower resistances were obtained.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, the results for CdS films on silicon nitride can be compared with literature data for CdS on other substrates. The resistivity values reported in the literature vary from 10 3 to 10 8 O cm [11][12][13][14][15] for chemical bath deposition to 10 À1 -10 3 O cm [16][17][18][19][20][21] for MOCVD grown and evaporated CdS and CdZnS films on glass.…”
Section: Resultsmentioning
confidence: 99%
“…4 Levels allocated in the range 0.27-0.32 eV have been reported for thin films prepared at different growth conditions and post-grown treatments. [17][18][19][20] In a second stage, the behavior for the same data vs. T Ϫ1/4 , as seen in the inset of Fig. 3, indicated that conduction is dominated by hopping through deep levels into the energy bandgap, and the variable range hopping model of Mott was satisfied for the as-grown samples at lower temperatures.…”
Section: Resultsmentioning
confidence: 72%
“…CdS thin films can be prepared by different techniques [4][5][6][7][8][9][10][11] such as thermal evaporation, close spaced sublimation, metal organic chemical vapor deposition (MOCVD), molecular-beam epitaxy (MBE), chemical bath deposition (CBD), chemical spray pyrolysis (CSP), electrodeposition and sputtering. Among these methods, thermal evaporation is one of the suitable methods for depositing large area thin film for solar cell application [12].…”
Section: Introductionmentioning
confidence: 99%